2020
DOI: 10.2337/dc19-2232
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial Evaluating the Efficacy and Safety of Fast-Acting Insulin Aspart Compared With Insulin Aspart, Both in Combination With Insulin Degludec With or Without Metformin, in Adults With Type 2 Diabetes (ONSET 9)

Abstract: To evaluate the efficacy and safety of fast-acting insulin aspart (faster aspart) compared with insulin aspart (IAsp), both with insulin degludec with or without metformin, in adults with type 2 diabetes not optimally controlled with a basalbolus regimen. RESEARCH DESIGN AND METHODS This multicenter, double-blind, treat-to-target trial randomized participants to faster aspart (n 5 546) or IAsp (n 5 545). All available information, regardless of treatment discontinuation or use of ancillary treatment, was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 11 publications
3
35
0
Order By: Relevance
“…This is conceptually similar to what was observed more than 20 years ago with the introduction of rapid‐insulin analogues . Trials in people with T2DM show a similar but lesser, yet statistically significant, reduction in the 1‐h PPG increment (mean decrease −0.40 to −0.59 mmol/L) compared with aspart . Despite reducing PPG levels in the trials reported, the overall glucose‐lowering ability of faster aspart compared with aspart (based on HbA1c levels) was comparable in T2DM or slightly better in T1DM .…”
Section: What Is the Potential Role For The Second‐generation Of Rapisupporting
confidence: 84%
See 3 more Smart Citations
“…This is conceptually similar to what was observed more than 20 years ago with the introduction of rapid‐insulin analogues . Trials in people with T2DM show a similar but lesser, yet statistically significant, reduction in the 1‐h PPG increment (mean decrease −0.40 to −0.59 mmol/L) compared with aspart . Despite reducing PPG levels in the trials reported, the overall glucose‐lowering ability of faster aspart compared with aspart (based on HbA1c levels) was comparable in T2DM or slightly better in T1DM .…”
Section: What Is the Potential Role For The Second‐generation Of Rapisupporting
confidence: 84%
“…Trials in people with T2DM show a similar but lesser, yet statistically significant, reduction in the 1‐h PPG increment (mean decrease −0.40 to −0.59 mmol/L) compared with aspart . Despite reducing PPG levels in the trials reported, the overall glucose‐lowering ability of faster aspart compared with aspart (based on HbA1c levels) was comparable in T2DM or slightly better in T1DM . SMPG profile data in several trials indicate that faster aspart has a minimal effect on reducing PPG after mixed meals.…”
Section: What Is the Potential Role For The Second‐generation Of Rapimentioning
confidence: 85%
See 2 more Smart Citations
“…Several faster aspart formulations with different combinations of niacinamide and zinc concentrations were tested in a clinical pharmacology trial, and, [16][17][18][19][20][21][22][23][24][25][26][27]. Moreover, phase III trials have investigated the efficacy and safety of faster aspart versus IAsp in subjects with T1D or T2D [28][29][30][31][32][33][34][35]. This review summarises the results from clinical pharmacology trials with faster aspart and relates these findings to the clinical benefits associated with faster aspart compared with IAsp based on outcomes from the phase III trials.…”
Section: Introductionmentioning
confidence: 99%